Suicidal Attempts as the Struggle Between Thanatos and Eros in "A Man Called Otto" - Ayunda Aprilian (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This research aims to analyze suicidal behavior experienced by the main character, Otto, in the movie “A Man Called Otto” from a psychological perspective. The study focuses on identifying the psychological factors that drive Otto’s suicidal ideation and repeated suicide attempts. This research employs a qualitative method, with data collected through careful observation and analysis of scenes, dialogues, and character actions in the movie. The analysis is conducted using Sigmund Freud’s psychological theory, particularly the concepts of the death instinct, life instinct, and the structure of personality consisting of the id, ego, and superego. The findings show that Otto’s suicidal ideation and attempts are rooted in deep grief following the loss of his wife, unresolved trauma, intense guilt, emotional exhaustion, and social alienation. Emotional triggers such as the loss of his child, removal from a leadership role, and feelings of being misunderstood strengthen the dominance of the death instinct, allowing destructive impulses to emerge while weakening the ego and intensifying self-blame. However, the presence of Marisol and her family gradually restores Otto’s emotional warmth, responsibility, and empathy. This marks the return of the life instinct through meaningful social interaction and new emotional bonds. Overall, Otto’s psychological journey shifts from domination by the death instinct toward a renewed sense of meaning and acceptance of life. Keywords: Psychological Approach, suicide, Thanatos, Eros